Synganglion histology in different stages of Rhipicephalus sanguineus ticks (Acari: Ixodidae) - Roma, Gislaine Cristina [UNESP]; Nunes, Pablo Henrique; Remedio, Rafael Neodini [UNESP]; Camargo-Mathias, Maria Izabel [UNESP] (Springer, 2012)
The present study performs a morpho-histological description of the central nervous system of Rhipicephalus sanguineus ticks in order to analyze if there are differences in this tissue among larvae, nymphs, and adults. The results showed that the central nervous system in all the life stages of R. sanguineus consists of a mass of fused nerves named synganglion. Externally, this organ does not present segmentation, consisting of a single structure located ventromedially in the third anterior of the body. This organ is externally covered by the neural lamella or neurilemma, a uniform and acellular layer. Below, there is the periganglionic membrane or perineurium, formed by glial cells, which are characterized by their elongated nuclei. The esophagus penetrates the synganglion dividing it in two regions: supraesophageal, which is the smaller of the two and consists of a protocerebrum, a single dorsal ganglion located anteriordorsally to the esophagus; and the subesophageal, which is the largest part of the synganglion, located in the posterior region and ventral to the esophagus. Internally, the synganglion is subdivided in an external cortical region-which contains the cellular body of the nervous cells-and an internal neuropile formed by a set of neural fibers and it is constituted by bilaterally symmetric ganglia, from where nerves emerge towards several parts of the body. The results here obtained showed that there are no differences in the morpho-histology of this tissue in different life stages of R. sanguineus, suggesting that the initial structure is maintained during the whole life cycle of the tick, i.e., from larval to adult stage.